1995
DOI: 10.1093/jnci/87.12.902
|View full text |Cite|
|
Sign up to set email alerts
|

Human Lung Carcinogen--DNA Adduct Levels Mediated by Genetic Polymorphisms In Vivo

Abstract: This study finds that the levels of two different carcinogen-DNA adducts vary in lung tissue (an important target tissue) in association with three separate genetic polymorphisms (i.e., CYP2D6, CYP2E1, and GSTM1). CYP2D6 and CYP2E1 genotypes are associated with higher 7-methyl-dGMP levels, while the GSTM1 null genotype is associated with higher numbers of PAH-dGMP adducts. These findings suggest that genetic polymorphisms are predictive of carcinogen-DNA adduct levels and would thus be predictive of an individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
2
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(84 citation statements)
references
References 0 publications
6
75
2
1
Order By: Relevance
“…For example, the greatest incremental lung cancer risk (sevenfold) for the 'susceptible' CYP1A1 genotype was seen in light smokers, whereas heavy smokers with this genotype had less than twice the risk of heavy smokers without the genotype . A study also showed that the increased level of carcinogen-DNA adduct related to genetic polymorphism was seen only in individuals exposed to levels of procarcinogens below the average level, while adduct levels in individuals exposed to higher levels were similar, regardless of the genetic status of their susceptibility genes (Kato et al, 1995). Thus, the significant effect seen with CYP1A1 in relation to breast cancer risk in our population, but not in Caucasian populations, might be due to the relatively lower levels of procarcinogens among Taiwanese women.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the greatest incremental lung cancer risk (sevenfold) for the 'susceptible' CYP1A1 genotype was seen in light smokers, whereas heavy smokers with this genotype had less than twice the risk of heavy smokers without the genotype . A study also showed that the increased level of carcinogen-DNA adduct related to genetic polymorphism was seen only in individuals exposed to levels of procarcinogens below the average level, while adduct levels in individuals exposed to higher levels were similar, regardless of the genetic status of their susceptibility genes (Kato et al, 1995). Thus, the significant effect seen with CYP1A1 in relation to breast cancer risk in our population, but not in Caucasian populations, might be due to the relatively lower levels of procarcinogens among Taiwanese women.…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione S-transferases and cytochrome P4501A1 Although early studies suggested a role of GSTM1 deficiency in aromatic-hydrophobic DNA adduct levels (Ryberg et al, 1994;Grinberg-Funes et al, 1994;Shields et al, 1993;Kato et al, 1995) these studies were criticized (Cuzick, 1995) for not defining cigarette smoking exposure adequately and for not having sufficient size to adjust for potential statistical artifacts. Continued work on the GSTs has appeared (Table 1) and more recent studies have included polymorphism of the GSTT1 and GSTP1 genes.…”
Section: Metabolic Polymorphismsmentioning
confidence: 99%
“…The CYP2D6-A allelic variant was detected using allele-specific double-step PCR according to Heim and Meyer (1990). The CYP2D6-B allele was identified using PCR and BstNI digestion as previously described by Kato et al (1995).…”
Section: Genotyping Of Gstm1 Cyp2d6 and Cyp1a1mentioning
confidence: 99%